2022
DOI: 10.1021/acs.macromol.2c00431
|View full text |Cite
|
Sign up to set email alerts
|

Episulfide Anionic Ring-Opening Polymerization Initiated by Alcohols and Primary Amines in the Presence of γ-Thiolactones

Abstract: Among the sulfur-containing polymers, polythioethers remains very attractive structures due to their high sulfur atom content, making them interesting candidates for various industrial applications, for example in the fields of energy storage or biomedical applications.Although anionic ring-opening polymerization of episulfides is known since decades, only a limited number of efficient initiating systems enable the synthesis of well-defined polymer chains. In this work, a one-pot, two step method was developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 58 publications
(144 reference statements)
0
9
0
Order By: Relevance
“…Polymerization experiments focused on the anionic ROP of thiirane derivatives revealed that simple and diverse nucleophiles can be utilized as initiators. 73 In particular, thiolate species derived from thiols have been demonstrated as promising initiators for the ROP of propylene sulfide (M34) (Scheme 15a), resulting in pure regiochemical regulation (i.e., head-to-tail microstructure) within the polymer backbone. [74][75][76] Interestingly, anionic ROP initiated by thiolates has been demonstrated to follow first order kinetics, hence possessing 'living' character.…”
Section: -Thiiranesmentioning
confidence: 99%
“…Polymerization experiments focused on the anionic ROP of thiirane derivatives revealed that simple and diverse nucleophiles can be utilized as initiators. 73 In particular, thiolate species derived from thiols have been demonstrated as promising initiators for the ROP of propylene sulfide (M34) (Scheme 15a), resulting in pure regiochemical regulation (i.e., head-to-tail microstructure) within the polymer backbone. [74][75][76] Interestingly, anionic ROP initiated by thiolates has been demonstrated to follow first order kinetics, hence possessing 'living' character.…”
Section: -Thiiranesmentioning
confidence: 99%
“…Very recently, BTL was used to introduce an ester linker between an hydroxy initiating compound and a polythioether chain. 66…”
Section: Thiolactone As a Thiolation Agentmentioning
confidence: 99%
“…Very recently, BTL was used to introduce an ester linker between an hydroxy initiating compound and a polythioether chain. 66 The group of Albertson studied the thiolation of hemicellulose using γ-thiobutyrolactone. 70 In the absence of a catalyst, hemicellulose hydroxyl groups are not sufficiently strong to undergo the 1,2-nucleophilic addition leading to the ringopening of the thiolactone ring.…”
Section: Bii Reaction Between Thiolactone and Alcohol-bearing Macromo...mentioning
confidence: 99%
See 2 more Smart Citations